Cognitive fatigue : multidisciplinary perspectives on current research and future applications - Ackerman, Phillip Lawrence, 1957- (APA science volumes., 2011)
"This book is based on a 3-day conference held at the Georgia Institute of Technology, Atlanta, in May 2009. The 14 invited chapter authors represent six countries and various university, government, and organizational laboratories. This book offers a contemporary panoramic snapshot of the field of cognitive fatigue research and applications. A wide array of theories and experimental methods are described, from mean effects to the study of individual differences and team performance, as are a variety of fatigue-related phenomena, ranging from neuroscience studies to examinations of laboratory and real-world behaviors and subjective feelings. The discussion sections after each chapter and in the last section of the book provide a rare glimpse into common and unique sources of theoretical and empirical progress in the field-the paradigm clashes and the points of common understanding that transcend this multidisciplinary field. The richness of the discussion reflects how the science progresses through challenges and disagreements, and also how scientists integrate research across areas to build more robust representations of empirical phenomena and search for new paradigms in which theories can be tested and generalized. Together, these chapters illustrate how much progress has been made in the field of cognitive fatigue, and they provide important sources of inspiration for future research and applications in the field"--Introduction. (PsycINFO Database Record (c) 2010 APA, all rights reserved).